Faecal bile acids are natural ligands of the mouse accessory olfactory system - Wayne I. Doyle (Nature Portfolio, 2016)
The accessory olfactory system (AOS) processes social chemosensory information and guides behaviors that are important for survival and reproduction in mammals. Here the authors report that mouse feces are a source of AOS neuronal activity and identify unconjugated bile acids in feces as a class of natural AOS ligands.